(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Evidences for an outermost prolonged diapause arose by keeping many secondinstar neanides of O. priesneri in vials filled with damp peat. Neanides were collected in April-May 2001 on flowering branches of Crataegus monogyna Jacq. and Cotoneaster horizontalis Decne (Rosaceae) in southern Italy; they built their cocoons within a few days and starved for several months before moulting. No of them did moult in spring 2002. Emergence of adults was observed in April-May 2003 (n=15) and in May 2004 (n=3). At last, 2 neanides did stay alive beyond spring 2005 and died many months later. As a whole, results suggest life-cycle of O. priesneri to be biennial and triennial. Possibly, the cycle may be longer to some extent. Because adult emergence was observed exclusively in spring, author thinks such prolonged diapause doesn’t depend upon the laboratory conditions. Literature on Thysanoptera doesn’t report any instance of neanides that starve for more than one year: up to now, a prolonged starvation (2 years) is ascribed only to adults of Stenothrips graminum Uzel and Thrips angusticeps Uzel.